Haematological Response of Catfish (Clarias sp.) to Variations in Stocking Density in a Bucket Aquaponics System - Pasaribu, Wesly; Fransira, Immaria; Santoso, Priyo; Tampa, Ahazia Imanuel (Sam Ratulangi University, 2025)
Determining the optimum stocking density is a key aspect of intensive catfish farming to maintain fish health and reduce mortality rates. This study aims to evaluate the effect of three stocking densities (20, 30, and 40 fish per bucket) on the hematological profile and mortality of catfish (Clarias sp.) in a bucket-based farming system. The fish were reared for 56 days, and blood samples were taken on days 0, 28, and 56 to measure total white blood cells (WBC), lymphocytes, monocytes, granulocytes, red blood cells (RBC), hemoglobin, hematocrit, and platelet count. Mortality was calculated at the end of the rearing period based on the initial number of fish and the number of live fish. Data were analyzed using one-way ANOVA followed by Tukey HSD test (p < 0.05). Results showed that on day 28, densities of 30 and 40 fish triggered a significant increase in WBC and lymphocytes compared to 20 fish, indicating a stress response and non-specific immune activation at high stocking densities. Chronically, SDM, hemoglobin, and some hematocrit values on days 28 and 56 were consistently lower at densities of 30 and 40 fish, while the lowest platelet count was found at a density of 30 fish. Cumulative mortality increased sharply from around 15% at a density of 20 fish to ±42% and ±56% at densities of 30 and 40 fish. The combination of hematology profiles and mortality showed that a density of 20 fish per bucket was the most physiologically and biologically feasible stocking density under the maintenance conditions used in this study. Keywords: Aquaponics, Catfish, Density, Hematology, Abstrak Penentuan padat tebar optimum merupakan aspek kunci dalam budidaya lele intensif untuk menjaga kesehatan ikan dan menekan tingkat kematian. Penelitian ini bertujuan mengevaluasi pengaruh tiga tingkat kepadatan (20, 30, dan 40 ekor per ember) terhadap profil hematologi dan mortalitas ikan lele (Clarias sp.) dalam sistem pemeliharaan berbasis ember. Ikan dipelihara selama 56 hari, dan pengambilan sampel darah dilakukan pada hari ke-0, 28, dan 56 untuk mengukur sel darah putih total (SDP), limfosit, monosit, granulosit, sel darah merah (SDM), hemoglobin, hematokrit, dan jumlah trombosit. Mortalitas dihitung pada akhir pemeliharaan berdasarkan jumlah ikan awal dan ikan hidup. Data dianalisis menggunakan One-way ANOVA diikuti uji Tukey HSD (p < 0,05). Hasil menunjukkan bahwa pada hari ke-28, kepadatan 30 dan 40 ekor memicu peningkatan signifikan SDP dan limfosit dibanding 20 ekor, mengindikasikan respon stres dan aktivasi imun non-spesifik pada padat tebar tinggi. Secara kronis, nilai SDM, hemoglobin, dan sebagian hematokrit pada hari ke-28 dan ke-56 konsisten lebih rendah pada kepadatan 30 dan 40 ekor, sedangkan trombosit paling rendah dijumpai pada kepadatan 30 ekor. Mortalitas kumulatif meningkat tajam dari sekitar 15% pada kepadatan 20 ekor menjadi ±42% dan ±56% pada kepadatan 30 dan 40 ekor. Kombinasi profil hematologi dan mortalitas menunjukkan bahwa kepadatan 20 ekor per ember merupakan padat tebar yang paling layak secara fisiologis dan biologis pada kondisi pemeliharaan yang digunakan dalam penelitian ini.. Keywords: Akuaponik, Budidakber, Hematologi, Kepadatan, Lele